Canons - Hallberg, Robert von (Chicago University of Chicago Press, 1984)
Canon formation: " . . . the traditional dream of ambitious critics. A canon is commonly seen as what other people, once powerful, have made and what should now be opened up, demystified, or eliminated altogether" So writes editor Robert von Hallberg in his introduction. This collection of essays articulates how canons are constructed and examines the ways in which academic canons influence literary thought and instruction. Presenting a wide range of canonical interpretation, the volume includes essays on such themes as Native American literature and the canon, the ideology of canon formation, the history of American poetry anthologies, undoing the canonical economy, the making of the modernist canon, and canon and power in the Hebrew scriptures.